Pengaruh Tingkat Perputaran Piutang Terhadap Profitabilitas Pada Koperasi Pondok Pesantren Al - Muhklisin Desa Lepak Kecamatan Sakra Timur 2012 -2016 - Muhamad Juani; Nurul Aini (Universitas Hamzanwadi, 2017)
In an increasingly globalized business world and rapid technological developments both information and communication led to the increasingly diverse needs of society. As a result the needs of masyarakatpun increasing and encouraging the growth of various types of companies and industries in Indonesia. In line with this, one company is expected to compete that is cooperative. Cooperative is a form of business entity that has a purpose like other business entities that provide welfare of members in particular and society in general. And do everything possible in order to survive and compete with other business entities. The problem in this research is to know how the influence of receivable turnover to profitability (return on equity). Does the receivable turnover rate have a significant effect on profitability (return on equity). During the period of 5 years (2012-2015). What we can know by going through the analysis will be done. The type of research used is quantitative research type that aims to determine the relationship between two or more variables, namely between receivables turnover and profitability (return on equity). As in the problem proposed is whether the receivable turnover has a significant effect on profitability (return on equity). To achieve the purpose of this study used a simple linear regression analysis tool while to test the hypothesis used t test. And the analysis result obtained by regression model Y = 1.029 + 0,660X this means that between variable X (Receivable Turnover) do not have influence to variable Y profitability (return on equity). Where the definition of simple linear regression that involves one independent variable as a predictor of the dependent variable. While significant results obtained that is equal to 0.362 which means receivable turnover does not have a significant effect on profitability (return on equity) because the rules for significance should be smaller than the number 0.05. The conclusion for this research is that receivable turnover does not have a significant effect on profitability (return on equity). with an insignificant number obtained from data processing. And this research can be used as a consideration by the Cooperative Pondok Pesantren Lepak Village, East Sakra district. Keywords: Receivable Turnover, Profitability (return on equity)